2015
DOI: 10.1186/s13690-015-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and morbidity patterns in under-five children with severe acute malnutrition (SAM) in Zambia: a five-year retrospective review of hospital-based records (2009–2013)

Abstract: BackgroundSevere acute malnutrition has continued to be growing problem in Sub Saharan Africa. We investigated the factors associated with morbidity and mortality of under-five children admitted and managed in hospital for severe acute malnutrition.MethodsIt was a retrospective quantitative review of hospital based records using patient files, ward death and discharge registers. It was conducted focussing on demographic, clinical and mortality data which was extracted on all children aged 0–60 months admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
103
15
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(150 citation statements)
references
References 18 publications
29
103
15
3
Order By: Relevance
“…This is similar with some previous studies [6,12,13], but it is inconsistent with study conducted in Colombia [14]. The difference may be due to difference in causes of malnutrition and life styles in the regions.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…This is similar with some previous studies [6,12,13], but it is inconsistent with study conducted in Colombia [14]. The difference may be due to difference in causes of malnutrition and life styles in the regions.…”
Section: Discussioncontrasting
confidence: 50%
“…The death rate after admission is higher. Study conducted in Zambia showed death rate after admission as 46% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Retarded growth is a condition that directly affects morbidity and mortality in childhood (8,9). According to World Health Organization data, pneumonia, diarrhea, malaria, measles and AIDs represent the cause of death in more than half of children under 5, and inadequate nutrition is present in one in three of these patients (10).…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted in South Africa showed that Case-fatality rate for SAM cases is remaining high 40.1% [4]. Likewise, another finding from Zambia revealed mortality rate 51% Vs 35% from 2009-2013 [5]. Thus, there needs exist for improved adherence to the WHO guidelines and periodic clinical audits to reduce death from childhood malnutrition [6].…”
Section: Introductionmentioning
confidence: 99%